The Excessive Use of “Screens” by Children - A Case Study for Developing Possible Therapeutic Approaches - Bisceanu, Florina Madalina (New Trends in Psychology, 2024)
The technological advances of the last 20 years have had a profound impact on modern society, bringing along important transformations. The advent of the internet, mobile phones and other remote communication devices has accelerated the exchange of information, exponentially increasing the amount of information being exchanged and processed by their users, which has put additional strain on cognitive capacities. Moreover, social changes have been observed, for example, with children and young people moving away from physical interaction towards a solitary lifestyle. Method- The online questionnaire method was used on a sample of 94 respondents. The results of the questionnaire will be discussed in this article. Results -This analysis includes the results of the questionnaire that led to the conclusions that will be stated in this article. Discussion and conclusions - Most psychologists believe that we are still far from obtaining scientific evidence on the duration of use of devices involving screens to be able to provide relevant recommendations for therapeutic approaches. The implications of excessive use of screen devices go beyond the realm of psychology and, as we shall see throughout this paper, imaging investigations on children and adolescents reveal a significant negative impact on the cortex, with tailored significance for each case studied, but more importantly, on the associated disorders that arise as a result of excessive screen time.